Sickle Cell Anemia: Variants in the CYP2D6, CAT, and SLC14A1 Genes Are Associated With Improved Hydroxyurea Response - Yahouédéhou, Sètondji Cocou Modeste Alexandre; Neres, Joelma Santana dos Santos; da Guarda, Caroline Conceição; Carvalho, Suellen Pinheiro; Santiago, Rayra Pereira; Figueiredo, Camylla Vilas Boas; Fiuza, Luciana Magalhães; Ndidi, Uche Samuel; de Oliveira, Rodrigo Mota; Fonseca, Cleverson Alves; Nascimento, Valma Maria Lopes; Rocha, Larissa Carneiro; et al. (Frontiers in Pharmacology, 2020)
Differences in hydroxyurea response in sickle cell anemia may arise due to a series of factors with genetic factors appearing to be predominant. This study aims to investigate the effects of single nucleotide polymorphisms in genes encoding drug-metabolizing enzymes and solute carriers on hydroxyurea response, in patients with sickle cell anemia. For that purpose, a total number of 90 patients with sickle cell anemia were recruited, 45 were undergoing hydroxyurea treatment, while 45 were not under the treatment. Association analyses were performed between CYP3A4 (rs2740574), CYP2D6 (rs3892097), CAT (rs7943316 and rs1001179) and SLC14A1 (rs2298720) variants and laboratory parameters. According to our findings, patients with hydroxyurea treatment demonstrated higher HbF levels and a significant improvement in hemolytic, hepatic, inflammatory and lipid parameters in comparison to those without the treatment. We also found significant associations between the CYP2D6 (rs3892097), CAT (rs7943316 and rs1001179) and SLC14A1 (rs2298720) variants and an improvement of the therapeutic effects, specifically the hemolytic, hepatic, inflammatory, lipid and renal parameters. In conclusion, our results highlight the importance of the investigated variants, and their strong association with hydroxyurea efficacy in patients with sickle cell anemia, which may be considered in the future as genetic markers.